PENCIPTAAN DAN PEMENTASAN KARAWITAN PAKELIRAN BARU DALAM PRESPEKTIF FEMINISME - Sukesi (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2021)
"Creation and Performance of New Karawitan in Feminism Paradigm" is a creative process in interpreting the development of karawitan in wayang performances that have developed recently. The position of women in the world of puppetry is only as stage decorations to become pesindhen, but this work tries to prove that the pesindhen can appear as a determinant of dramaturgy in wayang performances, not only as pesidnhen but also respond to the plot of the play with their creativity as a composer. The play used as a medium of musical expression is the story of "Ken Yasodha". Namely one of the female characters is a sindhen from Mandura. The puppeteer who is believed to be the perpetrator is Cahyo Kuntadi. Through this work, it proves that shadow puppet is not always attached to patriarchal culture, and can be worked on from the perspective of a pesindhen.